Implementasi Manajemen Pembelajaran Dalam Meningkatkan Hasil Hafalan Al-Quran - Al Arif, M Makruf; Zulfa, Mutiara; Suwandi, Suwandi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The purpose of this research is the planning, implementation, and evaluation of learning IBS Al Hamra Dau Malang. Qualitative approach with a single case study design; researchers as instruments; data sources include caretakers of Islamic boarding schools, heads of foundations, administrators, ustadz and students of Islamic boarding schools; data collection techniques with interviews, observation, and documentation. Learning planning for IBS Al Hamra Dau Malang in principle is equipped with a Learning Implementation Plan. The teaching and learning process is carried out every Monday-Friday, the ustadz conveys the subject matter using the classical material delivery method in four halaqoh, and ends with a deposit. Learning evaluation uses formative evaluation, namely an assessment in the form of a test carried out after one subject has been memorized by students and summative evaluation.